2019
DOI: 10.1186/s12984-019-0534-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of posture duration on hand tremor during tasks with attention-distraction in persons with Parkinson’s disease

Abstract: Background Tremor is one of the hallmarks and most bothersome symptoms in Parkinson’s disease (PD). The classical PD tremor is present at rest, but postural tremor also occurs. PD tremor can be continuous or intermittently present and can have a re-emergent nature. The tremor intensity is affected by attention and stress level. Observations of PD tremor have indicated increased tremor intensity with time during 30-s tremor assessments. This phenomenon has not previously been studied systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Each session started with 15-min of introduction and sharing, followed by 60-min of guided mindfulness meditation (30-min was facilitated with the use of singing bowls) and mindful breathing techniques, and 15-min of closing and sharing. Owing to the physical symptoms of PD patients including tremor, rigidity and bradykinesia, prolonged holding of the same pose is not recommended 44 . Hence, verbal cues of gentle movements were incorporated every 10-min during the guided meditation practice, so as to avoid exacerbation of physical symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Each session started with 15-min of introduction and sharing, followed by 60-min of guided mindfulness meditation (30-min was facilitated with the use of singing bowls) and mindful breathing techniques, and 15-min of closing and sharing. Owing to the physical symptoms of PD patients including tremor, rigidity and bradykinesia, prolonged holding of the same pose is not recommended 44 . Hence, verbal cues of gentle movements were incorporated every 10-min during the guided meditation practice, so as to avoid exacerbation of physical symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting TSA-OFF tremor severity was markedly lower during in the 0-15s bin thus the lower extent of tremor reduction compared to other bins was likely because there were fewer tremors at baseline. Overall the severity of tremors we observed was varied in time which is a well-characterized feature of PD 32 . Some postural tremors are known to have a ∼ 10s latency (i.e., reemergence 33 ) which could explain the 0-15s bin data.…”
Section: Resultsmentioning
confidence: 80%
“…Leodori et al, 12 using corticomuscular coherence and transcranial magnetic stimulation (TMS), have shown a causal relationship between primary motor cortex (M1) activity and re‐emergent tremor. Malling et al 13 showed that tremor intensity increase is associated with an increasing or gradually more synchronized cortico‐spinal drive. Conversely, levodopa, which is known to decrease tremor intensity, is associated with inhibitory activity in the cerebellar nucleus of the thalamus 8 …”
mentioning
confidence: 99%